Ribitol in Solution Is an Equilibrium of Asymmetric Conformations - Ohno, Shiho; Manabe, Noriyoshi; Yamaguchi, Takumi; Uzawa, Jun; Yamaguchi, Yoshiki (Molecules (Basel, Switzerland), 2021)
Ribitol (C5H12O5), an acyclic sugar alcohol, is present on mammalian α-dystroglycan as a component of O-mannose glycan. In this study, we examine the conformation and dynamics of ribitol by database analysis, experiments, and computational methods. Database analysis reveals that the anti-conformation (180°) is populated at the C3–C4 dihedral angle, while the gauche conformation (±60°) is seen at the C2–C3 dihedral angle. Such conformational asymmetry was born out in a solid-state 13C-NMR spectrum of crystalline ribitol, where C1 and C5 signals are unequal. On the other hand, solution 13C-NMR has identical chemical shifts for C1 and C5. NMR 3J coupling constants and OH exchange rates suggest that ribitol is an equilibrium of conformations, under the influence of hydrogen bonds and/or steric hinderance. Molecular dynamics (MD) simulations allowed us to discuss such a chemically symmetric molecule, pinpointing the presence of asymmetric conformations evidenced by the presence of correlations between C2–C3 and C3–C4 dihedral angles. These findings provide a basis for understanding the dynamic structure of ribitol and the function of ribitol-binding enzymes.